X‐ray photoemission spectroscopy investigation of Ce1 − xEuxCrO3 nano‐powders. (28th June 2016) - Taheri, M.; Konuma, M.; Razavi, F. S.
Abstract : To reveal the surface elemental composition and chemical states of the Ce1 − x Eu x CrO3 nano‐powders (x= 0.0, 0.3, 0.5, 0.7, 0.8, 1.0), X‐ray photoelectron spectroscopy was carried out in two conditions of before and after surface cleaning. This surface characterization described the core level binding energies of cerium, europium and chromium with different oxidation states. These results verified the morphology of the particles' surface which can be a confirmation of the spin disorder in these core‐shell structures. The effect of surface Ar sputtering on the oxidation states were studied. Copyright © 2016 John Wiley & Sons, Ltd.